Kemartiran Perempuan dalam Perspektif Teologi Feminis Kontemporer : Refleksi atas Bunda Maria dan Neerja Bhanot - Leopoldus Biliandri Antus; Eduardus Makung (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is driven by the prevalence of patriarchal perspectives within the Christian theological tradition, which frequently marginalises the role of women. Contemporary feminist theology emerges in this context as a critical effort to reinterpret women’s experiences of faith and suffering in light of God’s liberating love. This study analyses the martyrdom of the Virgin Mary and Neerja Bhanot as examples of witnessing to faith and humanity, affirming the spiritual power and courage of women in the face of patriarchal structures. The study employs a qualitative descriptive method, adopting a literature review approach to the Holy Scriptures, church documents and feminist theological literature. The results show that Mary’s martyrdom reflects quiet, prophetic faithfulness as a white martyr, while Bhanot displays universal humanitarian martyrdom. Both reveal a God who is present in love and solidarity with human suffering. This research affirms that feminist theology is a reflective praxis of liberation, demanding a transformation in the Church’s and society’s views on the dignity and role of women in the work of salvation.